Peran Kemampuan Komunikasi Matematika Terhadap Prestasi Belajar Matematika Siswa - Anggraini Astuti; Leonard Leonard (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2012)
The aim of this research is to know the influence of mathematical communication skills of the students toward the learning result (achievement) in junior high school in Jakarta. The research method which was used in the research is survey method. The population of research is all students in junior high school in Penjaringan, north Jakarta. Samples are taken by simple random sampling, consisted of 34 students. The research instrument is mathematical communication skills of the students and mathematics learning achievement. Data analysis employed regretion correlation. The hypothesis testing resulted in conclusion: there a positive correlation of mathematical communication skills of the students toward the mathematics learning achievement.